Tissue repair and regeneration in Drosophila imaginal discs. - Repiso, A.; Bergantiños, C.; Corominas, M.; Serras, F. (Development, Growth and Differentiation, 2011)
Exploring the mechanisms involved in tissue regeneration is one of the main challenges in biology and biomedicine. Multiple examples of tissue regeneration exist across the animal phyla, ranging from the recovery of the whole animal (e.g. flatworms) to the limited capability of the human liver. Studies performed in the 1960s showed that Drosophila imaginal discs are able to regenerate. This property, together with multiple genetic tools available, make fly an excellent model for the study of the regenerative process. Here we present an overview of the use of Drosophila for the study of regeneration and describe major recent advances in the understanding of this process. Current studies in Drosophila have unraveled some of the pathways and factors needed for a tissue to regenerate. Many observations point to the reuse of developmental programs and genetic reprogramming to drive regeneration. We discuss how this reprogramming could be orchestrated by the initial activity of the JNK pathway.